2012
DOI: 10.1038/nrneurol.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against infection in patients with multiple sclerosis

Abstract: Bacterial and viral infections have been shown to induce relapses and accelerate the progression of multiple sclerosis (MS). Vaccination to prevent communicable disease in such patients is, therefore, of key importance. Reports of potentially detrimental effects of immunization on the course of MS, however, have prompted patients and physicians to adopt a cautious attitude towards the use of vaccines. The risks associated with a number of vaccines have been investigated in patients with MS. Vaccines against so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 72 publications
1
52
0
14
Order By: Relevance
“…Overall, epidemiological data do not support a role of these viruses in the pathogenesis of MS though some controversy still holds concerning the safety of HBV vaccination [19][23]. Interestingly, Gregory et al (2012) [24] demonstrated that in the TNFRSF1A gene, which is part of the HBV interactome, the MS-associated variant directs increased expression of a soluble tumor necrosis factor receptor 1.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, epidemiological data do not support a role of these viruses in the pathogenesis of MS though some controversy still holds concerning the safety of HBV vaccination [19][23]. Interestingly, Gregory et al (2012) [24] demonstrated that in the TNFRSF1A gene, which is part of the HBV interactome, the MS-associated variant directs increased expression of a soluble tumor necrosis factor receptor 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, randomized, double-blind, placebo-controlled studies during the past decade have shown that influenza vaccination of MS patients neither increases the relapse rate nor worsens the course of disease [51]. Indeed, the administration of standard vaccines in MS patients is considered safe worldwide, it follows the same recommendations as in healthy adults and actually should be recommended to MS patients in order to avoid attacks of the disease [52]. Having all this in mind, it cannot be excluded that our data on the reduced level of secreted Abs in response to TLR7 stimulation can have a role in the exacerbation of relapses observed in MS-affected individuals along episodes of influenza infection.…”
mentioning
confidence: 99%
“…However no substantial evidence has been found to refute its use and due to the protection that such a vaccine may provide, it is still in general use. The vaccine against yellow fever has been suggested to exacerbate MS [12,13] whereas tetanus vaccine might even have a protective effect on its clinical course [1,7,14]. The HLA-DR2 haplotype has demonstrated linkage and association with susceptibility to multiple sclerosis, especially after hepatitis B vaccination [15,16].…”
Section: Discussionmentioning
confidence: 99%